Impact of Cyclones on the Sediment Dynamics and Coastal Morphology Changes in Bangladesh: A Comparative Study between Cyclone Sidr and Cyclone Mora (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The low-lying coastline of Bangladesh is highly vulnerable to tropical cyclones, which can cause extensive geomorphological changes and redistribute coastal sediments. This study investigates the differential impacts of two cyclones—Category-4 Cyclone Sidr (2007) and Category-1 Cyclone Mora (2017)—on sediment reworking and post-storm recovery at two distinct coastal sites: Kuakata (embayment with mangroves) and Sonadia Island (open, deltaic shoreline). Using sediment cores (n=16), we analyzed grain size distributions, geochemical properties (TOC, TN), and diatom assemblages to identify cyclone-induced overwash deposits and evaluate post-event accretion trends. At Kuakata, landward-thinning overwash layers (3–7 cm thick) composed of moderately sorted fine sand (101.8–149.5 μm, σϕ=1.70–2.01) and mixed marine-freshwater diatoms extended up to 375 m inland, highlighting the effect of storm surge moderated by mangrove cover. In contrast, Sonadia exhibited laterally scattered and thicker deposits (2–7 cm) with coarser sand (206.0–258.3 μm, σϕ=1.54–1.69), shaped by open topography and tidal reworking. Post-storm accretion rates were higher in Sonadia (up to 4.3 cm/year) than Kuakata (1.9 cm/year), driven by aeolian and fluvial processes. The findings underscore how cyclone intensity, coastal geomorphology, and vegetation jointly regulate sediment deposition and recovery. This research demonstrates the utility of sedimentological and microfossil proxies in reconstructing storm events and highlights the need for long-term coastal monitoring to enhance resilience planning under changing climate conditions.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 113-131